Novel sandwich immunoassay detects a shrimp AHPND-causing binary PirABVp toxin produced by Vibrio parahaemolyticus - Jeon, Min-Young; Han, Jee Eun; Lee, Dong Gwang; Cho, Young-Lai; Jang, Ju-Hong; Lee, Jangwook; Park, Jong-Gil; Kwon, Do Hyung; Park, Seon Young; Kim, Wantae; Lee, Kyunglee; Kim, Ji Hyung; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The binary PirA/PirB toxin expressed by Vibrio parahaemolyticus (PirABVp) is a virulent complex that causes acute hepatopancreatic necrosis disease (AHPND) in shrimps, affecting the global shrimp farming industry. AHPND is currently diagnosed by detecting pirA and pirB genes by PCR; however, several V. parahaemolyticus strains do not produce the two toxins as proteins. Thus, an immunoassay using antibodies may be the most effective tool for detecting toxin molecules. In this study, we report a sandwich ELISA-based immunoassay for the detection of PirABVp. Methods We utilized a single-chain variable fragment (scFv) antibody library to select scFvs against the PirA or PirB subunits. Phage display panning rounds were conducted to screen and identify scFv antibodies directed against each recombinant toxin subunit. Selected scFvs were converted into IgGs to develop a sandwich immunoassay to detect recombinant and bacterial PirABVp. Results Antibodies produced as IgG forms showed sub-nanomolar to nanomolar affinities (KD), and a pair of anti-PirA antibody as a capture and anti-PirB antibody as a detector showed a limit of detection of 201.7 ng/mL for recombinant PirABVp. The developed immunoassay detected PirABVp in the protein lysates of AHPND-causing V. parahaemolyticus (VpAHPND) and showed a significant detectability in moribund or dead shrimp infected with a VpAHPND virulent strain compared to that in non-infected shrimp. Discussion These results indicate that the developed immunoassay is a reliable method for diagnosing AHPND by detecting PirABVp at the protein level and could be further utilized to accurately determine the virulence of extant or newly identified VpAHPND in the global shrimp culture industry.